2020
DOI: 10.1186/s13023-020-01576-5
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic options for patients with rare rheumatic diseases: a systematic review and meta-analysis

Abstract: Background Rare diseases (RDs) in rheumatology as a group have a high prevalence, but randomized controlled trials are hampered by their heterogeneity and low individual prevalence. To survey the current evidence of pharmacotherapies for rare rheumatic diseases, we conducted a systematic review and meta-analysis. Randomized controlled trials (RCTs) of RDs in rheumatology for different pharmaco-interventions were included into this meta-analysis if there were two or more trials investigating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Additionally, seven antibiotics from different classes were tested in combination with antibacterial protein CB6-C. We found that antibacterial protein CB6-C showed synergy with ampicillin, and the combination with other antibiotics produced an additive effect. Some studies reported that the antibacterial effect of ciprofloxacin act on DNA gyrase and polymyxin B act on the cell outer membrane, enrofloxacin inhibit bacterial DNA replication, kanamycin inhibit protein synthesis, ampicillin inhibit cell wall synthesis, azithromycin inhibit bacterial transpeptide and rifampicin inhibits RNA synthesis [ 25 28 ]. Based on these antibiotic action mechanisms, the combination of antibacterial protein CB6-C and other antibiotics improved the binding efficiency and ultimately enhanced the antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, seven antibiotics from different classes were tested in combination with antibacterial protein CB6-C. We found that antibacterial protein CB6-C showed synergy with ampicillin, and the combination with other antibiotics produced an additive effect. Some studies reported that the antibacterial effect of ciprofloxacin act on DNA gyrase and polymyxin B act on the cell outer membrane, enrofloxacin inhibit bacterial DNA replication, kanamycin inhibit protein synthesis, ampicillin inhibit cell wall synthesis, azithromycin inhibit bacterial transpeptide and rifampicin inhibits RNA synthesis [ 25 28 ]. Based on these antibiotic action mechanisms, the combination of antibacterial protein CB6-C and other antibiotics improved the binding efficiency and ultimately enhanced the antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, while deep learning with, e.g., convoluted neural networks (CNNs) works well on images, they need large training data sets. These are difficult to obtain for rare diseases, which poses problems for most studies with rare diseases, including clinical trials [ 23 ]. Therefore, we searched for alternative approaches and decided to utilize Ružička similarity, which is a suitable measure to calculate similarity between images.…”
Section: Introductionmentioning
confidence: 99%